THE EFFECTIVENESS OF STEM BASED LEARNING IN IMPROVING SCIENTIFIC THINKING ABOUT GRADE V OF ELEMENTARY SCHOOL - Badarudin, Badarudin (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
This study is backgrounded by student’s scientific attitude which is still low in process of Natural Sciences in grade V SD/MI. The present study aimed to determine the improvement of scientific attitudes by using learning based on Science, Technology, Engineering, and Mathematics (STEM). This study is a class action research. Subjects of this study are students of class V in MI Muhammadiyah Kramat with a total of 20 students, consisting of 15 men and 5 women. The instrument used is a questionnaire and a scientific attitude observation sheet as well as a science learning achievement test. The results of this study there is an increase in scientific attitudes and learning achievement using the STEM model in grade V. Based on the questionnaire scientific attitude in the first cycle to get an average score of 3.7 or 74% which includes good criteria and then increased in the second cycle to get an average score of 4.2 or 84% which includes good criteria. Improvement of science learning achievement in the first cycle got an average value of 55.1 with 40.3% mastery learning and cycle II got an average value of 71.65 with 82% mastery learning. Each stage in STEM can facilitate the improvement of scientific attitudes in learning science in grade V SD/MI